Pedagogical Approaches, Instructional Practices, and Challenges in Teaching Literature among Senior High School Teachers - Columna, Sharime (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the pedagogical approaches, instructional practices, self-assessed utilization, influencing factors, and challenges in teaching literature among Senior High School teachers in Cluster 3, Division of Masbate Province. It was anchored in Constructivist, Behaviorist, and Connectivist Learning Theories and used a systems-based conceptual framework. A mixed-method design combined descriptive quantitative research with a phenomenological qualitative approach. Forty-four literature teachers from seventeen public secondary schools participated through complete enumeration, while fifteen teachers were purposively selected for interviews. Data were gathered using an adapted survey questionnaire, open-ended questions, and semi-structured interviews and were analyzed through frequency counts, percentages, weighted means, standard deviations, and thematic analysis. Findings showed that the Information-Based Approach was used most frequently (M = 4.89, SD = 0.32), followed by the Personal-Response Approach (M = 4.77, SD = 0.42). Teachers reported Proficient-to-Expert utilization across lesson stages, with the Moral-Philosophical Approach obtaining the highest overall self-assessment (M = 3.53, SD = 0.43). Retelling literary texts, checking comprehension, incorporating moral values, and identifying values from texts were practiced by all respondents. Approach selection was influenced by learner characteristics, curriculum requirements, instructional resources, professional experience, pedagogical beliefs, and sociocultural relevance. Major challenges included literacy and comprehension difficulties, low motivation and engagement, limited instructional time, large classes, inadequate resources, technology constraints, and insufficient professional preparation. The study concluded that literature instruction was competent and multifaceted but required a more coherent integration of approaches across lesson stages. It recommended adopting the Integrated Literature Instructional Guide anchored on the DepEd ILAW Framework, strengthening teacher training, and improving contextualized and multimedia resources. The study primarily supports SDG 4—Quality Education and also contributes to SDGs 9, 10, and 17 by promoting instructional innovation, equitable access to learning resources, and institutional collaboration. Its sustainability impact lies in strengthening inclusive, culturally responsive, technologically supported, and institutionally sustainable literature education.
Keywords: Deped ILAW Framework; Instructional Practices; Literature Instruction; Pedagogical Approaches; Teacher Competence; Teaching Challenges